Education on Keeping the School Environment Clean and Fostering Courage in Public Speaking at Anuban Wangmai Sasanasart School Satun Thailand - Azhar Nabilah; Tio Heriyana; Casnan; Nanan Abdul Manan; Hermawan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
In life, cleanliness is something that must be accustomed to and applied from an early age, both in the school environment and outside the school environment. In the school environment, students are taught and accustomed to selecting and sorting organic and non-organic waste. Learn how to use waste that allows you to produce something new in the context of recycling. In addition to environmental cleanliness, public speaking is also very important to be applied and trained from an early age. By capitalizing on public speaking students in public life will later easily express, and ideas innovations, ideas, and thoughts.